Therapeutic potential of SOX family transcription factors in osteoarthritis - Yue Huang; Zhuo Wang (Annals of Medicine)
Background As the worldwide population ages, osteoarthritis has significantly increased. This musculoskeletal condition has become a pressing global health issue and thus, prevention and treatment of osteoarthritis have become the primary focus of domestic and international research. Scholarly investigations of the molecular mechanisms that are related to the occurrence and development of osteoarthritis have shed light on the pathological causes of this condition to a certain extent, providing a foundation for its prevention and treatment. However, further research is necessary to fully understand the critical role of the transcription factor SOX9 in chondrocyte differentiation and the development of osteoarthritis. As a result, there has been widespread interest in SOX transcription factors. While SOX9 has been utilized as a biomarker to indicate the occurrence and prognosis of osteoarthritis, investigations into other members of the SOX family and the development of targeted treatments around SOX9 are still required.Purpose This article considers the impact of the SOX protein on the development and inhibition of osteoarthritis and highlights the need for therapeutic approaches targeting SOX9, as supported by existing research.Results SOX9 can contribute to the process of osteoarthritis through acetylation and ubiquitination modifications. The regulation of the WNT signalling pathway, Nrf2/ARE signalling pathway, NF-κB signalling pathway and SOX9 is implicated in the emergence of osteoarthritis. Non-coding RNA may play a role in the onset and progression of osteoarthritis by modulating various SOX family members, including SOX2, SOX4, SOX5, SOX6, SOX8, SOX9 and SOX11.Conclusion SOX9 has the capability of mitigating the onset and progression of osteoarthritis through means such as medication therapy, stem cell therapy, recombinant adeno-associated virus (rAAV) vector therapy, physical therapy and other approaches.